Pengaruh Perbankan Atas Pertumbuhan Ekonomi: Studi Kasus Bank Konvensional dan Bank Syariah di Indonesia - Rafsanjani, Haqiqi; Sukmana, Raditya (Universitas Brawijaya, Indonesia, 2014)
This paper examines the influence of banks (Conventional and Islamic) on economic growth in Indonesia during the period 2008-2012. Secondary data that were used in this research were in the form of monthly time series data during the year 2008-2012. The data were obtained based on monthly statistical banking report from Bank Indonesia (BI) and monthly statistical reports of the Monthly Industrial Production Index in the Large and Medium scale from Central Bureau of Statistics (BPS) of Indonesia. Total deposits, total loans/total financial, and total assets as variables that are representing the bank. GDP (Gross Domestic Product) is the variable that representing economic growth. By using Cointegration methods and Granger Causality, the result shows that generally, Conventional and Islamic banking affects economic growth in Indonesia.